Integrated analysis of intestinal microbial community and muscle transcriptome profile in rabbits - Shengbo Meng; Shanshan Xing; Huifen Xu; Jing Li; Yixuan Jiang; Hui He; Hanfang Cai; Ming Li (Animal Biotechnology)
Intestinal microbial community plays an important part in maintaining health and skeletal muscle development in livestock. This study is the first of its kind in the world. In order to better understand the relationship between gut microbiota and gene expression in skeletal muscle of rabbits, caecum contents and longissimus dorsi tissues of rabbits at 0 d (S1), 35 d (S2) and 70d (S3) were collected and subjected for 16S rRNA sequencing and transcriptome sequencing. Our results showed that, among three groups of rabbits, Firmicutes and Bacteroidetes were the dominant phyla at the phylum level, while Akmansia, Bacteroides and Ruminobacter were the dominant genera at the genus level, and the relative abundance of Akmansia and Bacteroides increased firstly and then decreased from 0 d to 70 d. By analyzing the transcriptome sequencing data, we identified 2866, 2446 and 4541 differentially expressed genes (DEGs) in S1 vs S2, S2 vs S3 and S1 vs S3 groups, respectively. Finally, we performed correlation analysis between gut microbiota and the expression levels of muscle development-related genes of rabbits at 0 d and 70 d. Compared with 0 day old rabbits, in 70 day old rabbits Acinetobacter and Cronbacter with decreased abundance, and Ruminococcaceae_UCG-014 and Ruminococcus_1 with increase abundance is beneficial to caecum health in rabbits. These results will lay a foundation for further re-searches about the relationship between caecum microflora and muscle development in rabbits.